Antecedents of Indian Green Consumer Behavior – A PLS-SEM Analysis Approach - Shalini Reddy Naini; M. Ravinder Reddy (Universitas Pasundan, 2023)
This study aims to determine the factors affecting the Indian green purchase intention (GPI) and examine the causal relationships between the identified determinants. The SPSS software has been used for the descriptive analysis, and the two-step analysis approach of the measurement and structural model is conducted in the SmartPLS. The results imply that multiple determinants influence the Indian consumers’ GPI, from the strongest to the weakest – green awareness, environmental attitude, green behavior, altruism, and interpersonal influence act as better predictors. The perceived environmental knowledge does not necessarily translate to the GPI. This study’s results will facilitate the industries in identifying the future purchasing factors scenario and incorporating the equivalent in their new product offerings. It also indicates that Indian consumers are more likely to indulge in green purchases if marketers in their product promotions and advertisements illustrate the consequences of their impact on the environment and the benefits of various green activities. This study is exclusive as it is the only study that has incorporated green awareness and green behavior as mediators along with the environmental attitude in studying the GPI.